Nickel mining on small islands and the conservation mandate: A regulatory review and policy analysis based on the Raja Ampat case study - Zahar, Wahyudi; Rosyid, Fadhila Achmadi (Journal of Engineering Researcher and Lecturer, 2025)
Indonesia plays a strategic role in global mineral supply, but the expansion of mining into coastal–small-island areas demand governance that balances down streaming objectives with the conservation mandate. This article presents a regulatory review and policy analysis illustrated by the Raja Ampat case. The policy framework examined includes Government Regulation (PP) No. 25 of 2024, Ministry of Energy and Mineral Resources Regulation (Permen ESDM) No. 15 of 2024, and Ministerial Decree (Kepmen ESDM) No. 177.K/MB.01/MEM.B/2024. The analysis shows that: (i) licensing and enforcement instruments have been strengthened, as reflected in corrective actions against non-compliant permits; (ii) in small-island contexts with high conservation value, the principal risks stem from sedimentation and declining water quality, which affect coral-reef ecosystems and fisheries–tourism livelihoods; and (iii) the effectiveness of regulations is highly determined by consistency of implementation, data traceability, and public participation. Policy recommendations include indicator-based enforcement (quarterly inspections and an RKAB compliance dashboard), a sediment-focused “AMDAL+” environmental impact assessment for coastal–reef settings, synchronizing a “small-island/geopark” filter in WIUP/WIUPK designation, supply-chain transparency, and strengthening local economic alternatives that are compatible with conservation. The findings affirm that a balance between economic growth and ecosystem sustainability can be achieved through a combination of stringent licensing screening, adaptive monitoring, and transparent governance.